Managing Time in the Workplace - Sara Walker; Allen Wysocki; Karl Kepner (EDIS, 2002)
This is EDIS document HR 014, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published May 2002.